The study of thermal comfort in a common commercial car cabin: looking at Malaysia’s perspective - Mohd Anas Mohd Sabri,; Chan, Zhao Jun; Nor Kamaliana Khamis,; Mohd Faizal Mat Tahir,; Wan Aizon Wan Ghopa,; Meor Iqram Meor Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Assessing thermal comfort in vehicles poses unique challenges compared to buildings. The in-car environment is characterized by specific factors such as sunlight exposure, poor clothing insulation, non-uniform average radiant temperature, and limited time to establish comfort parameters. To address these challenges, this study aims to evaluate thermal comfort in different branded car cabins by analyzing temperature distribution, air velocity, relative humidity, and dew point temperature. A comprehensive review of literature was conducted, focusing on various aspects including airflow regimes, factors influencing thermal comfort, measuring instruments, and comfort indices. Understanding these factors is crucial for developing comprehensive methodologies to assess thermal comfort and indoor air quality in vehicle cabins. The results of the study indicate that MPV cars offer superior comfort levels within the optimal range of -1 to +1, surpassing sedans and compact cars. These findings are instrumental in guiding design and engineering decisions to improve passenger comfort in vehicles. Tailoring the design of different car types to meet the specific comfort requirements can lead to enhanced overall comfort and satisfaction. In conclusion, this study provides valuable insights into assessing thermal comfort and indoor air quality in vehicle cabins. By addressing the unique challenges posed by the in-car environment, it offers guidance for designing and engineering vehicles that prioritize passenger comfort and well-being.